1986
DOI: 10.1172/jci112476
|View full text |Cite
|
Sign up to set email alerts
|

Assay of methylmalonic acid in the serum of patients with cobalamin deficiency using capillary gas chromatography-mass spectrometry.

Abstract: To determine the incidence of elevated levels of serum methylmalonic acid in patients with cobalamin deficiency, we utilized a new capillary gas chromatographic-mass spectrometric technique to measure methylmalonic acid in the serum of 73 patients with clinically confirmed cobalamin deficiency. Values ranged from 55 to 22,300 ng/ml, and 69 of the 73 patients had values above the normal range of 19-76 ng/ml as determined for 50 normal blood donors. In the cobalamin-deficient patients, serum methylmalonic acid w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
81
0
4

Year Published

1994
1994
2003
2003

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 163 publications
(88 citation statements)
references
References 24 publications
3
81
0
4
Order By: Relevance
“…Table 3 of the present study indicate that some elderly respondents with raised MMA levels also have abnormal plasma urea and creatinine concentration, and therefore impaired kidney function. Many other studies have also detected a link between raised blood MMA levels and impaired kidney function (Stabler et al, 1986;Rasmussen et al, 1990a, b;Joosten et al, 1993;Lindenbaum et al, 1994;Koehler et al, 1996;Norman, 1998Norman, , 1999van Asselt et al, 1998;Herrmann et al, 2000;Hvas et al, 2000). According to Whitehead et al (1994), the 97.5th centile of plasma creatinine in adults aged 25 -55 y is approximately 122 mmol=l (males) and 100 mmol=l (females), and for plasma urea it is 7.6 mmol=l (males) and 6.8 mmol=l (females).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Table 3 of the present study indicate that some elderly respondents with raised MMA levels also have abnormal plasma urea and creatinine concentration, and therefore impaired kidney function. Many other studies have also detected a link between raised blood MMA levels and impaired kidney function (Stabler et al, 1986;Rasmussen et al, 1990a, b;Joosten et al, 1993;Lindenbaum et al, 1994;Koehler et al, 1996;Norman, 1998Norman, , 1999van Asselt et al, 1998;Herrmann et al, 2000;Hvas et al, 2000). According to Whitehead et al (1994), the 97.5th centile of plasma creatinine in adults aged 25 -55 y is approximately 122 mmol=l (males) and 100 mmol=l (females), and for plasma urea it is 7.6 mmol=l (males) and 6.8 mmol=l (females).…”
Section: Discussionmentioning
confidence: 98%
“…Following the early studies that demonstrated the basic relationship between vitamin B 12 and MMA in man (Gompertz et al, 1967;Chanarin et al, 1973;Norman et al, 1982;Carmel, 2000), and which established reliable assay techniques for MMA (Stabler et al, 1986), were a number of key studies showing a surprisingly high prevalence of raised MMA levels in the plasma of older people, where it appeared to provide a more reliable indicator of functional vitamin B 12 status than serum or plasma vitamin B 12 concentrations per se (Lindenbaum et al, 1988;Rasmussen et al, 1989;Moelby et al, 1990;Joosten et al, 1993;Allen & Casterline, 1994;Lindenbaum et al, 1994;Koehler et al, 1996;Baik & Russell, 1999;Bjorkegren & Svardsudd, 1999;Herrmann et al, 2000). Clearly, the ageing process in itself, and the increasing prevalence of age-related medical conditions that impair vitamin B 12 absorption, both increase the probability that people will become vitamin B 12 -deficient as they grow older.…”
Section: Introductionmentioning
confidence: 99%
“…Cobalamin is a coenzyme in the conversion of methylmalonyl-CoA to succinyl-CoA [7,8]. In a situation with deficiency of cobalamin, methylmalonyl-CoA is converted to methylmalonic acid (MMA) rather than to succinyl-CoA [9].…”
Section: Introductionmentioning
confidence: 99%
“…A deficiency of dietary cobalamin leads to depressed tissue and plasma cobalamin concentrations (Stangl et al 2000). Additionally, the prolonged consumption of cobalamin-deficient diets (Stangl et al 2000), administration of cobalamin analogues (Stabler et al 1997), or the inactivation of cobalamin via nitrous oxide exposure ) can lead to the development of hyperhomocysteinemia via inhibition of methionine synthase and methylmalonicaciduria (Stabler et al 1997) via inhibition of methylmalonyl-CoA mutase.…”
mentioning
confidence: 99%